USING AGRI-FOOD WASTES AS POTENTIAL SUBSTRATES FOR XYLANASE PRODUCTION BY PENICILLIUM MENONORUM SP10 AND ITS APPLICATION IN CORNCOB SACCHARIFICATION - Luong, Thi Thu Huong; Prapasiri, Sarunpattori; Krachang, Cholthicha; Poeaim, Supattra (My University, 2025)
Xylanase is one of the key enzymes with wide spectrum application, especially in biomass saccharification. However, the xylanase production is still limited due to high processing costs. This study aimed to use agri-food wastes as substrates for Penicillium menonorum SP10’s xylanase production and investigate its capacity for corncob saccharification. The xylanase production was tested under solid-state fermentation using corncob, watermelon, passion fruit, lemon and orange peel substrates. Then, the corncob saccharification by P. menonorum SP10’s crude xylanase was optimized using a one-factor-at-time approach. The result indicates that P. menonorum SP10 could produce xylanase on agri-food waste substrates. The maximum xylanase activity was obtained on corncob with 45.35 U/mL after 7 days of incubation. Besides, P. menonorum SP10’s crude xylanase performed a high potential in corncob saccharification. It could release 6.08 mg/mL of reducing sugar under optimum conditions, including 0.4 g of substrate loading and temperature at 55℃ and pH 6 with an incubation time of 24 hours. Moreover, the hydrolysate’s sugar profile analysis on thin-layer chromatography indicated high glucose and xylose performances after saccharification. This study encouraged the reuse of agri-food wastes as cheap, abundant and nutrient substrates for xylanase production in the green, effective and economical direction.
Keywords: agri-food waste; corncob saccharification; xylanase production